Catalytic fast pyrolysis of lignocellulosic biomass - Liu, Changjun; Wang, Huamin; Karim, Ayman M; Sun, Junming; Wang, Yong (Chemical Society reviews, 2014)
Increasing energy demand, especially in the transportation sector, and soaring CO 2 emissions necessitate the exploitation of renewable sources of energy. Despite the large variety of new energy carriers, liquid hydrocarbon still appears to be the most attractive and feasible form of transportation fuel taking into account the energy density, stability and existing infrastructure. Biomass is an abundant, renewable source of energy; however, utilizing it in a cost-effective way is still a substantial challenge. Lignocellulose is composed of three major biopolymers, namely cellulose, hemicellulose and lignin. Fast pyrolysis of biomass is recognized as an efficient and feasible process to selectively convert lignocellulose into a liquid fuel-bio-oil. However bio-oil from fast pyrolysis contains a large amount of oxygen, distributed in hundreds of oxygenates. These oxygenates are the cause of many negative properties, such as low heating value, high corrosiveness, high viscosity, and instability; they also greatly limit the application of bio-oil particularly as transportation fuel. Hydrocarbons derived from biomass are most attractive because of their high energy density and compatibility with the existing infrastructure. Thus, converting lignocellulose into transportation fuels via catalytic fast pyrolysis has attracted much attention. Many studies related to catalytic fast pyrolysis of biomass have been published. The main challenge of this process is the development of active and stable catalysts that can deal with a large variety of decomposition intermediates from lignocellulose. This review starts with the current understanding of the chemistry in fast pyrolysis of lignocellulose and focuses on the development of catalysts in catalytic fast pyrolysis. Recent progress in the experimental studies on catalytic fast pyrolysis of biomass is also summarized with the emphasis on bio-oil yields and quality. We summarize the development of catalysts and provide the current understanding of the chemistry for catalytic fast pyrolysis of lignocelluloses biomass.